2010
DOI: 10.1073/pnas.0912340107
|View full text |Cite
|
Sign up to set email alerts
|

Response of an aerosol mass spectrometer to organonitrates and organosulfates and implications for atmospheric chemistry

Abstract: Organonitrates (ON) are important products of gas-phase oxidation of volatile organic compounds in the troposphere; some models predict, and laboratory studies show, the formation of large, multifunctional ON with vapor pressures low enough to partition to the particle phase. Organosulfates (OS) have also been recently detected in secondary organic aerosol. Despite their potential importance, ON and OS remain a nearly unexplored aspect of atmospheric chemistry because few studies have quantified particulate ON… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

46
577
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 529 publications
(624 citation statements)
references
References 46 publications
46
577
1
Order By: Relevance
“…(2)(3)(4)(5)(6)) and chemical ionization mass spectrometry (7)(8)(9), and the total of gas and aerosol RONO 2 (total Alkyl Nitrates, ΣAN) has been observed by Thermal Dissociation Laser Induced Fluorescence (TD-LIF) (1,(10)(11)(12). Recently there has been growing interest in understanding the partitioning of RONO 2 to atmospheric particles (13)(14)(15)(16)(17)(18). RONO 2 molecules with 2 -4 functional groups and a carbon backbone of ≥ C 4 have low enough vapor pressures to condense under ambient conditions and mechanistic studies show that RONO 2 can be among the most important molecules to SOA formation (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2)(3)(4)(5)(6)) and chemical ionization mass spectrometry (7)(8)(9), and the total of gas and aerosol RONO 2 (total Alkyl Nitrates, ΣAN) has been observed by Thermal Dissociation Laser Induced Fluorescence (TD-LIF) (1,(10)(11)(12). Recently there has been growing interest in understanding the partitioning of RONO 2 to atmospheric particles (13)(14)(15)(16)(17)(18). RONO 2 molecules with 2 -4 functional groups and a carbon backbone of ≥ C 4 have low enough vapor pressures to condense under ambient conditions and mechanistic studies show that RONO 2 can be among the most important molecules to SOA formation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However the most widely used methods for aerosol chemical characterization including Aerosol Mass Spectrometry (AMS) have had limited success. The difficulty of distinguishing inorganic and organic nitrates using AMS has been recently discussed in the literature (16)(17)(18). Nitrates have not yet been reported by Thermal Desorption Aerosol Gas-Chromatography (TAG) (25) or other methods of detailed realtime aerosol characterization.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory studies demonstrate that around 50 % of isoprene-derived particulate matter is associated with IEPOX production and uptake through the HO 2 pathway and in the presence of acidic aerosol particles (Liu et al, 2015). The existence of aerosol as seed particles seems to be necessary (Surratt et al, 2010;Lin et al, 2012), but also the 25 acidity of aerosol can influence the formation yield of IEPOX-SOA. Laboratory and field studies found a correlation between IEPOX-SOA and sulfate, which is related to the acidity of aerosol (Surratt et al, 2007;Budisulistiorini et al, 2013).…”
mentioning
confidence: 99%
“…Further oxidation of ISOPOOH may lead to isoprene epoxydiols (IEPOX), which then can partition into the particle phase by condensation or 20 reactive uptake and, thus, SOA derived from IEPOX (IEPOX-SOA) can be formed (e.g., Claeys et al, 2004;Carlton et al, 2009;Paulot et al, 2009;Surratt et al, 2010;Lin et al, 2012;Budisulistiorini et al, 2013;Worton et al, 2013;St. Clair et al, 2016;Liu et al, 2016b).…”
mentioning
confidence: 99%
See 1 more Smart Citation